Analysis of Public Perception of Canggu Village Infrastructure Facilities as a Tourist Destination - AAA Cahaya Wardani; Yudi Arimbawa; Made Novia Indriani; Cokorda Putra (Universitas Pendidikan Ganesha, 2026)
Canggu Village has undergone significant changes as a tourist destination. Changes in land use patterns influenced by tourism since the 1990s have affected the community's economic development. This study analyses community perceptions of the village's tourism spatial infrastructure. This study aims to analyse community perceptions of the infrastructure facilities in Canggu Village as a tourist destination. Using a mixed-methods embedded approach, this study combines qualitative and quantitative methods, with 50 pentahelix respondents selected through purposive sampling. Data collection was conducted through observation, in-depth interviews, documentation, and the distribution of questionnaires. The results show that the spatial infrastructure in Canggu Village is in the fairly good category, with an average value above 3.47 on a 5-point scale for most measured indicators. Community perceptions of the current condition of infrastructure facilities in Canggu Village generally indicate quite good results across basic, social, and economic infrastructure. However, it cannot be denied that tourism also brings its own challenges to the conditions in the Canggu area, where infrastructure development contributes to environmental degradation. This research implies that strategic and sustainable infrastructure development is a key factor in strengthening the competitiveness of tourist destinations and improving the community's economy as a whole.